PELATIHAN PERMINTAAN DAN PENAWARAN UNTUK SISWA/I PANTI ASUHAN ASIH LESTARI - Yusianto, Yusi; Yuniarwati, Yuniarwati; Sudirgo, Tony (Jurnal Bakti Masyarakat Indonesia, 2020)
This community engagement activity aims to provide demand and supply training in economics for students of the Asih Lestari Orphanage, West Jakarta. The provision of this training is to fulfill the demand of the manager of the Asih Lestari Orphanage in an effort to prepare their students for the national exams, especially in Economics. The participants consisted of 10 students, consisting of class IX students, class XI Akt Department (IPS) and Science Department, and class XII-Akt. However, given the time constraints, the training material will focus on the topic of demand and supply. In addition to being given an understanding of the concept of demand and supply also given examples of its application. After that, there are exercises and quizzes to see and assess students' understanding of the material presented. As a result, there was an increase in the scores of all participants between before and after the training, although overall, the results of the training were not satisfactory. Based on all material provided, the material on elasticity is considered the most difficult to understand because it has only been taught. The average value before training is 31.00, while the average value after training is 56.50. After the matter of elasticity is removed, the average value before training is 47.69, while the average value after training is 86.92. If the classification is made according to the class of students, the average grade of XI Science is the highest, which is 92.31. Understanding which is still relatively low on the material, cannot be entirely derived from students. School also determine whether the material provided is in accordance with the curriculum or not. In addition, students do not have supporting references for learning. For this reason, the institution can improve its library facilities so students can learn better. ABSTRAK: Kegiatan pengabdian pada masyarakat ini bertujuan untuk memberi pelatihan permintaan dan penawaran dalam ilmu ekonomi bagi siswa/i Panti Asuhan Asih Lestari, Jakarta Barat. Pemberian pelatihan ini untuk memenuhi permintaan pengelola Panti Asuhan Asih Lestari dalam upaya menyiapkan siswa-siswanya menghadapi ujian nasional, khususnya dalam mata pelajaran Ekonomi. Peserta terdiri dari 10 siswa/i, yang terdiri dari siswa kelas IX, kelas XI Jurusan Akt (IPS) dan Jurusan Science, dan kelas XII-Akt. Namun, mengingat keterbatasan waktu, materi pelatihan akan memfokuskan pada topik permintaan dan penawaran. Selain diberi pemahaman mengenai konsep permintaan dan penawaran juga diberikan contoh penerapannya. Setelah itu, diberikan latihan dan kuis untuk melihat dan menilai pemahaman siswa atas materi yang disampaikan. Hasilnya, terjadi peningkatan nilai semua peserta antara sebelum pelatihan dan setelah pelatihan, meskipun secara keseluruhan, hasil pelatihan kurang memuaskan. Berdasarkan semua materi yang diberikan, materi mengenai elastisitas dianggap paling sulit dipahami karena baru diajarkan. Nilai rata-rata sebelum latihan adalah 31,00, sedangkan nilai rata-rata setelah pelatihan adalah 56,50. Setelah soal materi elastisitas disingkirkan, maka nilai rata-rata sebelum latihan adalah 47,69, sedangkan nilai rata-rata setelah latihan adalah 86,92. Apabila dibuat klasifikasi menurut kelas siswa, maka nilai rata-rata kelas XI Science adalah yang tertinggi, yakni 92,31. Pemahaman yang masih relatif rendah terhadap materi, tidak dapat sepenuhnya berasal dari siswa/i. Tempat sekolah juga menentukan apakah materi yang diberikan sesuai dengan kurikulum atau tidak. Selain itu, siswa/i tidak memiliki referensi yang menunjang untuk belajar. Untuk itu, pihak panti dapat memperbaiki sarana perpustakaannya agar siswa/i dapat belajar lebih baik